An Oral-Based Study on Narrative Geographical Knowledge - BALCI, ALİ (EDAM, 2018)
This study aims to determine the geographical discourse that occurs in the personal histories of adults aged 75 years and older and how they interpret and use them. We conducted interviews with elderly persons living in Cemisgezek (Chemishkezek), a village established along the Karasu River, a branch of the Euphrates River. Expert opinions were taken on the duration, number and time of the interviews. Interview texts were analysed after they were read, by the researcher, to the participants, and approved. This information, subjected to content analysis to reveal the grandeur of the themes, was classified and interpreted, according to physical and human geographical characteristics. During analyses, care was taken to make direct quotations and use local phrases and expressions as spoken. Subjects covered in the discourse between researcher and interviewee included astronomy, location determination, finding direction, telling time, climatic elements, settlement location, view of dwellings, materials used for constructing houses, preferred rooms according to the seasons, crop cultivation, tree trimming, leaving land fallow and the use of streams. Geographical arguments, in the discourses that participants put into practice, agree with published geographical information. However, several expressions for stars and sea have fallen into disuse. We discuss these findings by comparing them with the literature.
Keywords: Narrative method; Oral geography; Geography in personal histories; Geography in narratives; Geographic education; CONCEPTUAL CHANGE